PENERAPAN PRINSIP EXCEPTIO NON ADIMPLETI CONTRACTUS DALAM PERKARA KEPAILITAN(STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO. 704 K/Pdt.Sus/2012 ANTARA PT. TELKOMSEL MELAWAN PT. PRIMA JAYA INFORMATIKA) - YULIA YULIA (PREMISE LAW JURNAL, 2015)
The principle of exceptio non adimpleti contractus only applies to a reciprocal contract, that is, an objection which states that a debtor does not accomplish the contract as it should be because the creditor himself has breached the contract. The file for bankruptcy of PT Telkomsel to PT Prima Jaya Informatika began when the cooperation agreement was breached, the objection to two purchase orders which caused the debt of PT Telkomsel. The principle of exceptio non adimpleti contractus was regulated in the cooperation agreement. It is recommended that in the same case as it has been mentioned above, the panel of judges have the same point of view in reaching a verdict on such a case; their verdict should not only be based on legal provisions but also on jurisprudence. Keywords: exceptio non adimpleti contractus, bankruptcy, telkomsel